EDUCATIONAL TOURISM IN THE TRAINING OF FUTURE TOURISM PROFESSIONALS - Dembovska, Iveta; Silicka, Inese; Ļubkina, Velta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The concept of educational tour (field trip) and the importance and role of  educational tours in the training of future tourism professionals are explored and analysed in the paper. The concept of educational tourism is formulated and the types of field trips are identified in the result of the research. A sociological survey with the aim to find out opinions of tourism students on the necessity, preferable types, and duration of field trips was conducted as well.Research methods: the logical construction method, scientific induction, synthesis, the monographic method, methods of quantitative and qualitative analysis for processing the survey results.